2023
DOI: 10.1080/14616696.2022.2163276
|View full text |Cite
|
Sign up to set email alerts
|

Subjective social status in places that don’t matter: geographical inequalities in France and Germany

Abstract: In recent decades, the rise of the service economy and the growing attractiveness of large cities have created new social inequalities within countries, which have been seen as a source of resentment for people living in the "places that don't matter". We study spatial inequalities in terms of subjective social status using a measure of the place in the social hierarchy that individuals believe they occupy in France (1999France ( -2017 and Germany (1992Germany ( -2021 on the basis of data from the Internationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Specifically, access to jobs (Rothstein, 2019) and consequently migration to places where jobs are available (Buscha et al, 2021;Sprung-Keyser et al, 2022) have been associated with better chances of upward mobility. In Europe, different regions face dramatically different growth profiles, with some struggling to uphold and improve prosperity for their residents (Diemer et al, 2022;Vigna, 2023).…”
Section: Local Labor Marketsmentioning
confidence: 99%
“…Specifically, access to jobs (Rothstein, 2019) and consequently migration to places where jobs are available (Buscha et al, 2021;Sprung-Keyser et al, 2022) have been associated with better chances of upward mobility. In Europe, different regions face dramatically different growth profiles, with some struggling to uphold and improve prosperity for their residents (Diemer et al, 2022;Vigna, 2023).…”
Section: Local Labor Marketsmentioning
confidence: 99%
“…Similar dynamics are also observed within countries and between sub-national regions. Vigna (2023) showed how, in France and Germany, individuals in peripheral regions, far from large urban centres and with lower levels of economic development, show consistently lower levels of subjective social position. In addition, the temporal development of structural inequality ensures different opportunities for upward mobility in different contexts and at different times, influencing the relationship between the situation of origin and the current situation (Nolan & Weisstanner, 2022).…”
Section: The Role Of Contextual Inequalitiesmentioning
confidence: 99%
“…If we somewhat depart from classical socio-economic status theory (Ganzeboom et al, 1992), subjective social position represents something very useful: it potentially detects in a single score the result of the interrelation and juxtaposition of individual identities. This question has been widely related to health and well-being but is well-established in the sociological literature (Gidron & Hall, 2017Nolan & Weisstanner, 2022;Oesch & Vigna, 2022, 2023. The presence of very few generic reference points -'top' and 'bottom'makes it easily comparable across time and space (Evans & Kelley, 2004), but doubts have been raised as to what the question really detects (Evans & Tilley, 2017).…”
Section: Subjective Social Positionmentioning
confidence: 99%
“…People are embedded in specific local contexts, and there is reason to believe that judgments of their social class can be influenced by these contexts (Destin et al, 2017). For instance, research has shown that French and German people living in urban areas perceive their social status as higher than others with similar objective positions living in rural areas (e.g., Vigna, 2023). As another example, individuals in more affluent contexts are more prone to perceiving themselves as higher class compared to those with comparable positions in less prosperous contexts (e.g., Evans & Kelley, 2004; but also see Andersen & Curtis, 2012).…”
Section: Formation Of One's Subjective Social Classmentioning
confidence: 99%